Feasibility Study of Rice Farming Investment Using Adol Oyodan Land Rental System - Anggara, Muhammad Fariskan; Mahananto; Prasetyo, Agung; Anwaristi, Aprilia Yuanita (Journal of Rural and Urban Community Studies, 2025)
This study aims to find out the agricultural land lease system for farmers in Ketaon Village, Banyudono District, Boyolali Regency, and to determine the feasibility of rice farming in the land lease system in Ketaon Village, Banyudono District, Boyolali Regency. The location of the research was carried out in Ketaon Village, Banyudono District, Boyolali Regency. Sampling was carried out using purposive sampling. This research was carried out within 5 planting seasons because in 2 years it consisted of 6 planting seasons; 1 planting season could not be done because there was an improvement in irrigation. The analysis method used is quantitative descriptive. The data analysis used is descriptive analysis and investment analysis. The result of this study is that the agricultural land rental system carried out by the average farmer in Ketaon Village, Banyudono District, Boyolali Regency, is with the adol oyodan land rental system. This rental system is a land rental system where tenants give money in advance directly to the owner of agricultural land (rice fields). This land lease system is worth continuing to strive for this because based on the calculations that have been carried out, it shows from several calculations both through the calculation of NPV (Net Present Value) 20.814.535, IRR (Internal Rate of Return) 100%+, Net Benefit Cost Ratio 3,4779, Gross Benefit Cost Ratio (Gross B/C)2,2033 shows a positive value and meets the eligibility requirements for the farming business carried out.